Culturally Relevant Resilience: A Psychometric Meta‐Analysis of the Child and Youth Resilience Measure (CYRM). (15th July 2020) - Renbarger, Rachel L.; Padgett, R. Noah; Cowden, Richard G.; Govender, Kaymarlin; Yilmaz, Münübe Z.; Scott, Lakia M.; Makhnach, Alexander V.; Novotny, Jan Sebastian; Nugent, Geoff; Rosenbaum, Lacey; Křeménková, Lucie
Abstract : Measuring key components of resilience is vital for understanding cross‐cultural dynamics among youth and the environment. The Child and Youth Resilience Measure (CYRM‐28) was developed as a cross‐cultural measure of resilience and has been used globally. To examine the cross‐cultural utility of the CYRM‐28, we conducted a systematic review of the literature reporting on the psychometric properties of the measure. Using data representing six countries ( N  = 6, 232) that were supplied from authors of the studies reviewed, a multilevel confirmatory factor analysis was also conducted to estimate the variability of the measurement properties among communities, ages, and sex. Results indicate that the literature generally did not include reliability and validity information for the instrument. From the multilevel confirmatory factor analysis, the measure was invariant between adolescent age‐groups and sexes but not across communities.